THE FEDERAL GOVERNMENT ACCOUNTANTS ASSOCIATION. - Gustafson, George A. (The Accounting Review, 1962)
The Federal Government Accountants Association (FGAA) needs no introduction to many accountants and auditors. However, since the FGAA has "come of age," it is believed that a few words about its organization, aims, and accomplishments would be timely. The FGAA is a non-profit, professional, and educational organization, incorporated in the District of Columbia, with 34 local chapters located in most major cities in the U.S. There are also four chapters abroad, in Frankfurt, Germany; Tokyo, Japan; Pans, France; and Balboa, Canal Zone. It is an organization of Federal administrative or policy advisory employees with accounting and auditing backgrounds. The Association has several purposes. It aids in the improvement of budgeting, accounting, reporting, and auditing techniques by providing a medium for the free interchange of ideas among accountants and financial management personnel in the Federal service. The complex nature of Governmental affairs creates the need for an Association of this caliber.